The Legal Framework for Electronic Signature in Jordan A Comparative Study with EU Regulations - Al Animat, Mohammad Elayan Karim (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
Electronic signature, owned by the owner is a matter of trust, and it may be difficult for the other contracting party to verify its authenticity , hence the importance of dealing with and organizing digital signature is of paramount importance., The aim of this study is to compare the legislation of the EU and Jordan in governing the responsibility of the authentication service provider concerning electronic signature, to find out whether there is a lack of organized legislation with regard to the work of electronic signature service providers. The article will also examine the adequacy of general regulations in supervising the duties of electronic service providers under Jordanian law. I will emphasize the importance of establishing specific regulations, and the need to establish special rules for this particular responsibility, especially with regard to the development of specific rules in line with the UNCITRAL model law on electronic signatures. As regards the EU directives on electronic signatures and other international legislations, it must be emphasized that the issue of electronic authentication services raises several legal problems that can be resolved. Among others the legal nature of the liability of electronic authentication service providers, their legal basis, and their establishment are still subject to legal controversy. In addition to the scope of this responsibility and the issue of determining the extent of compensation that can be imposed in the event of harm to the customer or others, the Jordanian legislators have not established a specific legal system for the responsibility of the employer and the electronic authentication provider to clarify all the ambiguities to which electronic banking operations are exposed to in order to create an independent and sustainable legislative environment for all the rapid technological development.